(untitled) - Gironiére, Paul P. De La (Manila, 1962)
Contents: Description of Manilla, continued prosperity in practice, hunting the stag Indian mode of chasing the wild buffalo,...
Keywords: Philippines,Philippines; Mô tả và du lịch,Description and travel